Analisis Diplomasi Digital Kementerian Luar Negeri terkait Indonesia’s Chairmanship pada KTT ASEAN 2023 - Permatasari, Diah ayu; Samad, M. Yusuf; Persadha, Pratama Dahlian (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2024)
The handover the ASEAN Chairmanship to Indonesia brought Indonesia as a host of ASEAN Summit 2023 held in Labuan Bajo, NTT. In the preparation of this event, Indonesia’s Ministry of Foreign Affairs utilized social media as a tool for digital diplomacy. This study aims to analyze the digital diplomacy efforts of the Indonesia’s MoFA through its official X account, @Kemlu_RI, which has demonstrated higher activity compared to the Ministry's Instagram and Facebook accounts. This study used a qualitative approach, utilizing content analysis and a critical paradigm. Data collection is conducted using the Anaconda Navigator application, which facilitates the management and analysis of the data. The findings indicate that the application of digital diplomacy at this event represents an initial milestone compared to previous ASEAN Summits. It has effectively supported Indonesia's position in multilateral forums and enhanced its public presence. However, the study also reveals that  the implementation of dialogic communication principles has been suboptimal, particularly in terms of responding to comments or questions from netizens.